2020
DOI: 10.1111/pai.13423
|View full text |Cite
|
Sign up to set email alerts
|

Parental questionnaires provided reliable data on childhood asthma compared with national registers

Abstract: Background Much of our knowledge of childhood asthma comes from questionnaire‐based studies. Our main aim was to assess the agreement between parental‐reported data at 12 years of age and data from two national Swedish registers. Methods Data were obtained from the prospective, longitudinal, population‐based Children of Western Sweden cohort, which focused on children born in 2003. The parents answered questionnaires at six months and one, four, eight and 12 years of age. Personal identity numbers linked 3634 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…The data in this study indicate that national registers underestimate the prevalence of AR diagnosis and the use of AR medication. This is in contrast to an earlier study, where data from the same cohort showed good agreement between questionnaire data on asthma medication and the SPDR 28 . On the contrary, in that study, the NPR provided incomplete information on asthma diagnoses, most likely because visits to primary care were not included 28 .…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The data in this study indicate that national registers underestimate the prevalence of AR diagnosis and the use of AR medication. This is in contrast to an earlier study, where data from the same cohort showed good agreement between questionnaire data on asthma medication and the SPDR 28 . On the contrary, in that study, the NPR provided incomplete information on asthma diagnoses, most likely because visits to primary care were not included 28 .…”
Section: Discussioncontrasting
confidence: 84%
“…28 On the contrary, in that study, the NPR provided incomplete information on asthma diagnoses, most likely because visits to primary care were not included. 28 The value of highly validated national registers is undeniable, and they can provide reliable data for many but not all diagnoses. 10 Register data on AR can supplement questionnaire data.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The response rate was 68.5% (5605/8176) at 6 months and 68.9% (4987/7241) at 12 months (4941 completed both questionnaires). The cohort has previously been described, 3,15 including flow charts of the study 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…The cohort has previously been described, 3,15 including flow charts of the study. 15,16 Information on the introduction of complementary feeding was collected at 12 months of age. The questions on the introduction of complementary feeding are given in Table S1.…”
Section: Participants Born In 2003mentioning
confidence: 99%